A Theory of Securities Markets Under Uncertainty - Dieffenbach, Bruce C. (Review of Economic Studies, 1976)
Journal Article A Theory of Securities Markets Under Uncertainty Get access Bruce C. Dieffenbach Bruce C. Dieffenbach University of Pennsylvania Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 43, Issue 2, June 1976, Pages 317–327, https://doi.org/10.2307/2297327 Published: 01 June 1976